Evaluating the Effectiveness of the SQ3R Method in Enhancing Students' Reading Proficiency - Firda Wulan Sudarsono; Astutik, Yuli (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Background: Reading proficiency plays a pivotal role in language acquisition, influencing comprehension levels. However, while the SQ3R method has been identified as a tool for enhancing reading skills, its practical application and effectiveness in high school English settings are insufficiently studied, revealing a significant research gap. Methodology: This research employs a mixed-methods approach utilizing the Quan-qual model to address this gap comprehensively. Quantitative methods entail a true experimental design involving control and experimental groups, with 54 class X students purposively sampled. Additionally, qualitative data were collected through interviews with four representative students. Findings: The findings reveal the effectiveness of the SQ3R method in improving reading achievement, supported by significant score enhancements in reading tests. Interviews with students also indicate positive attitudes toward SQ3R, boosting their motivation for reading. These results emphasize SQ3R's potential to elevate high school students' reading skills and enhance engagement in English language learning. Conclusion: This study underscores the effectiveness of the SQ3R method in enhancing reading achievement among high school students. Utilizing a mixed-methods approach, it reveals substantial score enhancements in reading tests and positive student perceptions, indicating increased motivation for reading. These findings highlight SQ3R's potential to elevate reading proficiency and engagement in English language learning, offering valuable insights for educators and curriculum development. Originality: The research identifies a gap in the exploration of the SQ3R method's application in high school English language learning, particularly regarding its effectiveness and students' perceptions. Further investigation is necessary to delve into qualitative aspects and involve diverse samples for a comprehensive understanding of English language learning in high school contexts.